An integrated biomimetic array chip for establishment of collagen‐based 3D primary human hepatocyte model for prediction of clinical drug‐induced liver injury. Issue 12 (13th September 2021) - Xiao, Rong‐Rong; Lv, Tian; Tu, Xia; Li, Peiwen; Wang, Tiantian; Dong, Haiheng; Tu, Pengfei; Ai, Xiaoni
Abstract: Drug‐induced liver injury (DILI) is a leading cause of therapy failure in the clinic and also contributes much to acute liver failure cases. Investigations of predictive sensitivity in animal models have limitations due to interspecies differences. Previously reported in vitro models of liver injury based on primary human hepatocytes (PHHs) cannot meet the requirements of high physiological fidelity, low cost, simple operation, and high throughput with improved sensitivity. Herein, we developed an integrated biomimetic array chip (iBAC) for establishing extracellular matrix (ECM)‐based models. A collagen‐based 3D PHH model was constructed on the iBAC as a case for the prediction of clinical DILI at throughput. The iBAC has a three‐layer structure with a core component of 3D implanting holes. At an initial cell seeding numbers of 5000–10, 000, the collagen‐based 3D PHH model was optimized with improved and stabilized liver functionality, including cell viability, albumin, and urea production. Moreover, basal activities of most metabolic enzymes on the iBAC were maintained for at least 12 days. Next, a small‐scale hepatotoxicity screening indicated that the 3D PHH model on the iBAC was more sensitive for predicting hepatotoxicity than the 2D PHH model on the plate. Finally, a large‐scale screening of liver toxicity using 122 clinical drugs further demonstrated that the collagen‐based 3D PHH model on the iBAC had superior predictive sensitivity compared to all previously reported in vitro models. These results indicated the importance of 3D collagen for liver physiological functionality and hepatotoxicity prediction. We anticipant it being a promising tool for risk assessment of drug‐induced hepatotoxicity with a widespread acceptance in drug industry. Abstract : A collagen‐based 3D primary human hepatocyte model on an integrated biomimetic array chip for the prediction of clinical drug‐induced liver injury was developed. Industrialized validation of liver toxicity using 122 clinical drugs demonstrated that this model had superior predictive sensitivity compared to all previously reported in vitro models. The improved sensitivity indicated the importance of the 3D collagen for liver physiological functionality and hepatotoxicity prediction.